(untitled) (Research, Society and Development, 2021)
Affection is present in all human spheres, from social relationships, through the human development process and also through cognitive processes, such as those developed in the school environment. This work aims to understand the importance of affectivity in the teacher-student relationship and its influence on the teaching and learning processes, understanding that, just as in different social spheres, the way the educator manages his relationship with the student will influence the social interactions of the class, in the academic performance of the students, as well as in the student’s own further development. From the objective described above, we developed this research also in order to answer the motivating question of this study, which is: how affectivity can influence the student-teacher relationship in the teaching and learning processes? Finally, the bibliographical study now undertaken will be organized around three axes, namely: knowing the different perspectives on the affectivity category; dialogue about the nature of teaching and learning processes; and, finally, understanding affectivity as a pedagogical presupposition for the relationship between teacher-student. Thus, as a result of this research, we highlight the importance of positive affects within the classroom environment and, more precisely, in the relationship between educator and student, as affectivity and cognition are not dissociated. Therefore, the affections permeated in this interpersonal relationship can generate decisive impacts on the teaching and learning process, as well as facilitating or hindering them.